indonesia Hubungan Tingkat Pengetahuan Dan Sikap Dengan Perilaku Masyarakat Dalam Pemilahan Sampah Rumah Tangga Di Desa Medahan Blahbatuh Gianyar Tahun 2025: Relationship Between Level Of Knowledge And Attitude With Community Behavior In Household Waste Sorting In Medahan Village Blahbatuh Gianyar In 2025 - Ni Luh Putri Padmayani; I Ketut Aryana; I Gusti Ayu Made Aryasih; I Nyoman Sujaya (Jurnal Kesehatan Lingkungan (JKL), 2026)
Title: Relationship Between Level Of Knowledge And Attitude With Community Behavior In Household Waste Sorting In Medahan Village Blahbatuh Gianyar In 2025 Background: In Indonesia, waste sorting still problems occurs today. Medahan Village is one of the author's destinations. The purpose of this study was to determine whether there is a relationship between the level of knowledge and attitude with community behavior in sorting their household waste. Method: The method used in this study is the cross-sectional method. Result: The results obtained were 31 people with the last education of junior high school and 26 people with the last education of high school. The age of the sample in this study was less than 50 years, from 57 people the age ratio obtained was 37 - 49 years. Knowledge results obtained 57 people (100%) with good values. Attitude results obtained 43 people (75.4%) with good values and 14 people (24.6%) with poor values. Behavior obtained results of 27 people (47.4%) with good values and 30 people (52.6%) with poor values. Conclusion: It can be concluded that the relationship between attitude and behavior are one of the relationships that can be said to have a significant relationship between attitudes and community behavior in sorting household samples because the calculated x2 obtained a greater result than the x2 table, which means that Ho is rejected and Ha is accepted.